Practical Approach for the Determination of Response Factors of Impurities in Drugs by HPLC - Dharmendra Kushwah; Haresh B. Patel; Praveen K. Sinha; Pijush K. Jana (E-Journal of Chemistry)
For the determination of accurate quantity of impurities in the samples authentic impurity standards or response factors at a given wavelength must be known. In the presented work a convenient method for determination of relative response factors of impurities has been described without using an authentic impurities standard. An approach for the determination of response factors of the impurities where impurity standard is physically not available was developed and verified using different approaches. One such method was developed and verified by RP-HPLC using Cosmosil C18 MS-II column at UV 238 nm. Two different approaches were employed and the verification of correctness of approach was done using a known related substance of known response factor.